Effects of treadmill grade and speed on medial gastrocnemius muscle activity in chronic stroke patients - Roghayeh Mohammadi (Majallah-i ̒Ilmī-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Simnān, 2017)
Introduction: Plantarflexor muscles produce propulsive force in the second half of stance phase; deficient motor output from these muscles would lead to inadequate propulsion at push off phase of gait following stroke. It is important to develop strategies to improve plantarflexor output. This study examined the effects of walking on a treadmill at varying gradients and speeds on medial gastrocnemius (MG) muscle activation in stroke survivors.